THE HISTORY AND CULTURE OF RIMPU AS MBOJO REGIONAL IDENTITY - Raihany, Vinny; Jumardi, Jumardi (Kementerian Pendidikan dan Kebudayaan, 2021)
Bima society (Mbojo) is a combination of various tribes, ethnics and cultures. Bima area (Mbojo) is an area that is famous and abundant because of its culture and customs as identity and characteristics of Bima society. One of several cultures which is still preserved by Bima society in West Nusa Tenggara is Rimpu. The purpose of this study was to find out the history and culture of Rimpu as an identity among women Mbojo in Bima, West Nusa Tenggara. This study was compiled using qualitative research from documentation studies in the form of scientific articles and the results interviews conducted with the local people of Bima (Mbojo). The result study showed that Rimpu is a dress as a cover for Muslim women at that time and became identity and characteristic of the Mbojo area. Since the entry of Islam in Bima Kingdom, Rimpu was used as a tool to communicate the values, hopes, and beliefs of group community that was followed by its members. Rimpu has many benefits and uses. Rimpu is divided into two types, namely ordinary RimpuÂ and mpida Rimpu.